2020
DOI: 10.1007/s42729-020-00311-0
|View full text |Cite
|
Sign up to set email alerts
|

N2O Emissions Mitigation in Acidic Soil Following Biochar Application Under Different Moisture Regimes

Abstract: Managing soil pH has been recognized as one of the promising options for N 2 O emission mitigation in acidic soils. Rice-straw biochar (BC) application to acidic soils can not only ameliorate soil acidity but also influence N 2 O emissions. We investigated the impact of various levels of rice-straw-derived biochar, a control (no biochar), 2% biochar, and 4% biochar under 50% and 90% water-filled pore space (WFPS) values. In comparison with the application of biochar at 2%, the application of biochar at 4% more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Soil types and P and K fertilizers were the key factors affecting N 2 O emissions from paddy soils. Soil type affecting N 2 O emissions was a reasonable finding because varied pH values, nutrient status, and textures would influence N 2 O emissions, and the K fertilizer application rate affected N utilization for the plant to grow, thus potentially changing the N 2 O emission response to N fertilizer [14,46,47]. Neutral to slightly acidic soil pH favored N 2 O emissions (Supplementary Materials Figure S10).…”
Section: Discussionmentioning
confidence: 93%
“…Soil types and P and K fertilizers were the key factors affecting N 2 O emissions from paddy soils. Soil type affecting N 2 O emissions was a reasonable finding because varied pH values, nutrient status, and textures would influence N 2 O emissions, and the K fertilizer application rate affected N utilization for the plant to grow, thus potentially changing the N 2 O emission response to N fertilizer [14,46,47]. Neutral to slightly acidic soil pH favored N 2 O emissions (Supplementary Materials Figure S10).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, our research found that biochar application increased soil pH (Figure 2). The increased pH in the FB treatment enhanced the activity of nitrous oxide reductase and promoted the reduction from N 2 O to N 2 [44,45]. Moreover, biochar played an important role in transferring electrons to denitrifying microorganisms, promoting the conversion of N 2 O to N 2 , and thus reducing N 2 O emissions [46].…”
Section: Effects Of Environmental Factors On N 2 O Emissionsmentioning
confidence: 99%
“…The paper provides data that the use of biochar together with nitrogen fertilizers in rice sowing increases the yield of rice up to 44.4% [18]. Biochar obtained from rice straw normalizes the pH of acidic soil, reduces N 2 O emissions into the environment by 83% and activates mineral nitrogen [19]. The authors have studied the nature of sorption/desorption of biourea by biochar obtained from rice husk and straw at different pyrolysis temperatures (300, 450, 600°C), it has been found that the maximum adsorption of urea has been shown by biochar from rice straw and husk obtained at a pyrolysis temperature of 450°C, and these composites have the potential to enhance agricultural yield through the efficient use of nitrogen.…”
Section: Issn 2224-5286mentioning
confidence: 99%